FLT3 tyrosine kinase inhibitors in acute myeloid leukemia: clinical implications and limitations. Issue 2 (February 2014) - Kayser, Sabine; Levis, Mark J.
Abstract Internal tandem duplications of the FMS-like tyrosine kinase 3 (FLT3) gene are one of the most frequent gene mutations in acute myeloid leukemia (AML) and are associated with poor clinical outcome. The remission rate is high with intensive chemotherapy, but most patients eventually relapse. During the last decade, FLT3 mutations have emerged as an attractive target for a molecularly specific treatment strategy. Targeting FLT3 receptor tyrosine kinases in AML has shown encouraging results in the treatment of FLT3 mutated AML, but in most patients responses are incomplete and not sustained. Newer, more specific compounds seem to have a higher potency and selectivity against FLT3. During therapy with FLT3 tyrosine kinase inhibitors (TKIs) the induction of acquired resistance has emerged as a clinical problem. Therefore, optimization of the targeted therapy and potential treatment options to overcome resistance is currently the focus of clinical research. In this review we discuss the use and limitations of TKIs as a therapeutic strategy for the treatment of FLT3 mutated AML, including mechanisms of resistance to TKIs as well as possible novel strategies to improve FLT3 inhibitor therapy.